A retrospective review of pregnancies on biologics for the treatment of dermatological conditions. (2nd June 2020) - Boggs, J. M. E.; Griffin, L.; Ahmad, K.; Hackett, C.; Ramsay, B.; Lynch, M.
Abstract: Psoriasis often first presents in young adulthood, with the average age of diagnosis in women being 28 years, thus in the prime reproductive years. In addition, approximately 50% of pregnancies worldwide are unplanned. Although biologic therapies have revolutionized the treatment of moderate‐to‐severe psoriasis, there are no controlled studies of biologics in pregnant women. The increasing use of these agents in women of childbearing age highlights the need to further assess their safety during pregnancy. Postmarketing experience regarding the safety of these drugs is accumulating and being published, with largely reassuring results. We present our real‐world experience of 17 pregnancies occurring in women on treatment with biologic agents for dermatological conditions to further add to the body of knowledge.